2014
DOI: 10.1039/c3ta15439d
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient photoelectrochemical response by sea-urchin shaped ZnO/TiO2 nano/micro hybrid heterostructures co-sensitized with CdS/CdSe

Abstract: ZnO/TiO2-based hybrid heterostructures co-sensitized with CdS and CdSe showed remarkable PEC response while offering efficient scattering of sunlight in the visible frequency domain, and efficient electron–hole separation and transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Thus, tuning and matching the band energetics of the two NCs are critical to achieve efficient charge transfer and transport. Charge separation between the different semiconductor NCs has been intensively studied in CdSeTiO 2 and CdSZnO systems 1216. These studies revealed that photoexcited charge injection from CdSe (or CdS) to TiO 2 (ZnO) was possible by using visible‐light irradiation because of the narrow band gap of CdSe (or CdS).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tuning and matching the band energetics of the two NCs are critical to achieve efficient charge transfer and transport. Charge separation between the different semiconductor NCs has been intensively studied in CdSeTiO 2 and CdSZnO systems 1216. These studies revealed that photoexcited charge injection from CdSe (or CdS) to TiO 2 (ZnO) was possible by using visible‐light irradiation because of the narrow band gap of CdSe (or CdS).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ZnO nanostructures with metallic shell-layers (Ag, Au, Ni, Co) have exhibited interesting device properties as: photocatalysts202122, photoelectrochemical anodes2324, sensors25, DNA detectors26, and dye sensitized electrodes272829. On the other hand, ZnO nanostructures passivated with other semiconductors (TiO 2 , CdS, ZnS, InN, SiO 2 ) have also shown multifunctional applications3031323334. Significantly, in all cases, the passivation layer over ZnO nanostructures plays different roles, including: surface defect states neutralizer, environmental or chemical protector, carrier separator, absorbability enhancer, and electrical signal amplifier35.…”
mentioning
confidence: 99%
“…11 (B), it can be seen that an appropriate structure was obtained after energy level redistribution. It is obvious that the cascade structure was the stepwise positions of band edges based on the redistribution of CdS and Ag 2 S due to align Fermi levels [46][47][48]. Both the energy levels of the conduction band and the valence band of the CdS layer are lower than that of the Ag 2 S layer, therefore, a gradient energy level structures was formed in CdS/ Ag 2 S nanostructure.…”
Section: Morphology and Properties Of G/cds/ag 2 S Nanofilmsmentioning
confidence: 97%